Immunization with recombinant fusion of LTB and linear epitope (40–62) of epsilon toxin elicits protective immune response against the epsilon toxin of Clostridium perfringens type D - Kaushik, Himani; Deshmukh, Sachin Kumar; Solanki, Amit Kumar; Bhatia, Bharti; Tiwari, Archana; Garg, Lalit C. (AMB Express, 2019)
Epsilon toxin (Etx) produced by Clostridium perfringens types B and D, a major causative agent of enterotoxaemia causes significant economic losses to animal industry. Conventional vaccines against these pathogens generally employ formalin-inactivated culture supernatants. However, immunization with the culture supernatant and full length toxin subjects the animal to antigenic load and often have adverse effect due to incomplete inactivation of the toxins. In the present study, an epitope-based vaccine against Clostridium perfringens Etx, comprising 40–62 amino acid residues of the toxin in translational fusion with heat labile enterotoxin B subunit (LTB) of E. coli , was evaluated for its protective potential. The ability of the fusion protein rLTB.Etx 40–62 to form pentamers and biologically active holotoxin with LTA of E. coli indicated that the LTB present in the fusion protein retained its biological activity. Antigenicity of both the components in the fusion protein was retained as anti-fusion protein antisera detected both the wild type Etx and LTB in Western blot analysis. Immunization of BALB/c mice with the fusion protein resulted in a significant increase in all isotypes, predominantly IgG1, IgG2a and IgG2b. Anti-fusion protein antisera neutralized the cytotoxicity of epsilon toxin both in vitro and in vivo. Thus, the results demonstrate the potential of rLTB.Etx 40–62 as a candidate vaccine against C. perfringens .